2022
DOI: 10.1037/pro0000415
|View full text |Cite
|
Sign up to set email alerts
|

Stigma toward people with severe mental disorder in university students before and after their practicum program in mental health.

Abstract: University education affects the attitudes of future professionals toward people with mental illness. To evaluate and compare stigmatizing attitudes of university students from nursing, psychology, and occupational therapy careers toward people with severe mental disorder (SMD), a multisite, nonrandomized, pre-post-test design was used with evaluations before and after a practicum program in mental health. Evaluation was done on a convenience sample of 520 students. The Mental Illness Clinicians' Attitudes (MI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…In Spain, studies with university students have shown that medical and nursing students had more negative attitudes than psychology and occupational therapy students in several stigmarelated themes: recovery, dangerousness, uncomfortability, disclosure, and discriminatory behavior (27). In another study evaluating the effect of internships in the last courses in the degrees of nursing, psychology and occupational therapy, results showed that although the effect was significant in the reduction of stigma toward people diagnosed with severe mental disorder in the degrees of nursing and psychology, it was small (28). Spanish teaching students have also participated in stigma studies.…”
Section: Introductionmentioning
confidence: 99%
“…In Spain, studies with university students have shown that medical and nursing students had more negative attitudes than psychology and occupational therapy students in several stigmarelated themes: recovery, dangerousness, uncomfortability, disclosure, and discriminatory behavior (27). In another study evaluating the effect of internships in the last courses in the degrees of nursing, psychology and occupational therapy, results showed that although the effect was significant in the reduction of stigma toward people diagnosed with severe mental disorder in the degrees of nursing and psychology, it was small (28). Spanish teaching students have also participated in stigma studies.…”
Section: Introductionmentioning
confidence: 99%
“…When comparing the stigma present in psychology students with students from other faculties, it has been found that the latter had a more negative perception of people with mental health problems, reacted worse emotionally to them and showed more avoidance behaviours (Bannatyne & Stapleton, 2017;Ruíz et al, 2022;Saavedra & Murvatian, 2021). Studies that have compared students who begin their psychology studies with students who have advanced in their degree and, therefore, have taken subjects related to the clinical or practical part, have obtained that there are either no differences in the level of stigma, remaining at a mild or moderate level (Fresán et al, 2012) or it decreases when acquiring knowledge, but still persists to a significant degree (Economou et al, 2017;Grandón et al, 2022).…”
Section: Introductionmentioning
confidence: 99%